2021
DOI: 10.3389/fsurg.2021.613812
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Mini-Percutaneous Nephrolithotomy in Patients Under the Age of 18: An Experience With 112 Cases

Abstract: Purpose: Renal calculi are becoming more common among children. Although, extracorporeal shock wave lithotripsy (ESWL) is the first choice in this age group, minimal invasive surgeries, such as percutaneous nephrolithotomy (PCNL), are indicated for some patients. Recently, PCNL devices have become smaller in size with acceptable efficacy and lower complications. We evaluated the outcomes and complications of mini-PCNL (MPCNL) surgery in our referral training centers.Materials and Methods: Between September 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…Two recent studies have also confirmed mini PCNL's efficacy and safety to be done towards children with urinary tract stones. [34][35] This study was a pilot meta-analysis on the efficacy and safety of mini PCNL for pediatric nephrolithiasis. A limitation of this study is that it lacked sufficient resources, including only two studies for all quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have also confirmed mini PCNL's efficacy and safety to be done towards children with urinary tract stones. [34][35] This study was a pilot meta-analysis on the efficacy and safety of mini PCNL for pediatric nephrolithiasis. A limitation of this study is that it lacked sufficient resources, including only two studies for all quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Интерес вызывает зарубежная публикация 2021 г. по использованию миниПНЛ, где критериями включения авторы сделали сл. показатели: камни в почках более 10 мм и предшествующая неудача ДУВЛ в анамнезе, возраст до 18 лет (в результатах ранжирования по возрастам не приводится, отмечается только, что пациентов в возрасте менее 5 лет было несколько), нормальная функция почек [15]. Также ряд авторов приводят различные данные по размеру камня почки (от 1 до 2 см) как критерия включения, для предпочтения выполнения ПНЛ перед ДУВЛ или ретроградной интраренальной хирургией (РИРХ) [16][17][18][19][20][21][22].…”
Section: результатыunclassified